Standard Urine Collection Bag as an Improvised Bogotá Bag as a Temporary Abdominal Closure Method in an Open Abdomen in Preventing Abdominal Compartment Syndrome - Ahmed Shabhay; Zarina Shabhay; Kondo Chilonga; David Msuya; Theresia Mwakyembe; Samwel Chugulu (Case Reports in Surgery)
Primary abdominal wall closure post laparotomy is not always possible. Certain surgical pathologies such as degloving anterior abdominal wall trauma injuries and peritoneal visceral volume and cavity disproportion render it nearly impossible for the attending surgeon to close the abdomen in the first initial laparotomy. In such surgical clinical scenarios leaving the abdomen open might be lifesaving. Forceful closure might lead to abdominal compartment syndrome and impair respiratory status of the patient. Open abdomen closure techniques have evolved over time from protection of abdominal viscera to complex fascia retraction prevention techniques. Silo bags, i.e., (Bogotá Bags), are relatively cheap, available materials used as a temporary abdominal closure method in limited resources settings. Despite its limitations of not preventing fascia retraction and draining of peritoneal fluid, it protects the abdominal viscera. We report a case of a 29-year-old male who developed incisional anterior abdominal wall wound dehiscence. He was scheduled for emergency explorative laparotomy. Intraoperatively, multiple attempts to reduce grossly dilated edematous bowels into the peritoneal cavity and fascia approximation into the midline were not possible. A urinary collection bag was sutured on the skin edges as a temporary abdominal closure method in prevention of abdominal compartment syndrome. He fared well postoperatively and eventually underwent abdominal incisional wound closure. In emergency abdominal surgeries done in limited surgical material resource settings were primary abdominal closure is not possible at initial laparotomy, sterile urine collection bags as alternatives to the standard Bogota bags as temporary abdominal closure materials can be safely used. These are relatively easily available and can be safely used until definite surgical intervention is achieved with relatively fewer complications.